Ultrasound versus convection cooking of beef longissimus and pectoralis muscles - Pohlman, F.W.; Zayas, J.F.; Dikeman, Michael E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Longissimus and pectoralis muscles were removed from 10 steer carcasses at 4 days postmortem , aged for 14 days at 4 ̊F, then assigned to either ultrasound (ULS) or convection (Conv) cooking to either 144 or 15 8 ̊F internal temperature. Ultrasound cooking was faster (P<.05), had greater (P<.05) moisture retention and less (P<.05) cooking loss, and used less energy (P<.05). It also produced muscle samples that required less (P<.05) peak force to shear than those from Conv cooking and resulted in superior (P<.05) myofibrillar tenderness. No significant interactions occurred among cooking method, muscle, or endpoint temperature. As expected, longissimus (ribeye) muscles cooked faster (P< .05) and required less (P<.05) energy and were superior (P<.05) in instrumentally measured texture and sensory tenderness than pectoralis muscles. Cooking to 158EF caused greater (P<.05) moisture and cooking losses, required more (P<.05) time and energy, and degraded (P<.05) instrumental textural and sensor y characteristics. Ultrasound offers a new cooking mode that could increase cooking speed, improve energy efficiency and improve some textural characteristics, compared to conventional cooking.
Keywords: Beef; Ultrasound cooking; Endpoint temperature; Tenderness